Trans-resveratrol-loaded nanostructured lipid carrier formulations for pulmonary drug delivery using medical nebulizers - Iftikhar, Khan (2025)
Aerosolization is a non-invasive approach of delivering drugs for both localized and systemic effects, specifically pulmonary targeting. The aim of this study was to deliver trans-resveratrol (TR) as an anti-cancer drug entrapped in a new generation versatile carriers nanostructured lipid carrier (NLC) to protect degradation and improve bioavailability via medical nebulizers. Twelve TR-NLC (i.e., F1-F12) formulations were prepared using different combinations and ratios of formulation ingredients via hot high-pressure homogenization. Upon analysis, formulations F1 and F2 demonstrated a particle size of <185 nm, a polydispersity index (PDI) <0.25, Zeta potential values of ∼30 mV and an entrapment efficiency >94%. The aerosolization performance of the F1 and F2 formulations was performed via a next generation impactor (NGI), using medical nebulizers. The air jet nebulizer demonstrated lower drug deposition in the earlier stages (1-2) and significantly higher deposition in the latter stages 3-5 (for both formulations), targeting middle to lower lung deposition. Moreover, the air jet nebulizer exhibited significantly higher emitted dose (ED) (87.44 ± 3.36%), fine particle dose (FPD) (1652.52 ± 9.68 µg) fine particle fraction (FPF) (36.25 ± 4.26%), and respirable fraction (RF) (93.41 ± 4.03%) when the F1 formulation was used as compared to the F2 formulation. Thus, the TR-NLC F1 formulation and air jet nebulizer were identified as the best combination for the delivery and targeting peripheral lungs.